2003
DOI: 10.1093/aje/kwg039
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Self-Report of Vitamin and Mineral Supplement Use in the Vitamins and Lifestyle Study

Abstract: In the United States, dietary supplements contribute a large proportion of micronutrient intakes. Therefore, it is important to collect accurate information on supplement use for studies of micronutrients and disease risk. This report describes the test-retest reliability and validity of a detailed, self-administered mailed questionnaire on vitamin and mineral supplement use. Participants (n = 220) completed the questionnaire at baseline and 3 months later. During an in-person interview, participants provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
127
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 39 publications
3
127
2
Order By: Relevance
“…Next, they reported whether they took a single nutrient supplement of h-carotene, vitamin A, vitamin C, or vitamin E, and if yes, the frequency and usual dose (amount per day). Daily intake of each nutrient was calculated as follows: frequency (days per week) Â dose per day / 7 (days) (30). For these analyses, participants are categorized as ''nonusers'' or ''users'' of dietary supplements from this instrument.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, they reported whether they took a single nutrient supplement of h-carotene, vitamin A, vitamin C, or vitamin E, and if yes, the frequency and usual dose (amount per day). Daily intake of each nutrient was calculated as follows: frequency (days per week) Â dose per day / 7 (days) (30). For these analyses, participants are categorized as ''nonusers'' or ''users'' of dietary supplements from this instrument.…”
Section: Methodsmentioning
confidence: 99%
“…This open-ended approach is more valid than selfadministered questionnaires (30). Average daily nutrient intake from the inventory was calculated as follows: frequency (days per week)  number of pills taken each time  dose per pill / 7 (30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there have been a few studies on dietary supplement assessment methodology. [5][6][7]11,21,[24][25][26][27] It is important to develop generally accepted assessment method in the dietary supplement study to make direct comparison.…”
Section: Dietary Supplement Use In Japanmentioning
confidence: 99%
“…This method has been used as the reference method to assess the validity of self-reported dietary supplement use in other studies. 31,32 The definition of asthma was based on self-report, which is subject to recall bias and misclassification. However, it is not feasible for large epidemiological studies such as NHANES to validate all self-reported medical histories.…”
mentioning
confidence: 99%